Fuzzy inventory model with two warehouses under possibility constraints - Maiti, Manas Kumar; Maiti, Manoranjan (Fuzzy sets and systems, 2006)
A multi-item inventory model with two-storage facilities is developed with advertisement, price and displayed inventory level-dependent demand in a fuzzy environment (purchase cost, investment amount and storehouse capacity are imprecise). The model is formulated as a single/multi-objective programming problem under fuzzy constraint. Constraints are satisfied with some pre-defined necessity and the problem is solved via the Goal Programming Method (GPM) when crisp equivalents of the constraints are available and by a fuzzy simulation-based single/multi-objective genetic algorithm (FSGA/FSMOGA) otherwise. The model is illustrated with some numerical examples and results from different methods are compared in some particular cases.